(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The problem of groundwater pollution by heavy metals creates acute and chronic health hazards to the rural populace who rely on this untreated sources to meet their daily water needs. This paper presents a comprehensive seasonal heavy metal pollution risk assessment and human health risk analysis of twenty hand-dug wells in three municipal districts: Uffa, Itua, and Ugbogbo in Igarra town, Akoko-Edo Local Government Area, Northern Edo State, Nigeria. Water samples collected in the wet season (July 2011) and dry season (December 2011) were analyzed for eight trace metals: copper (Cu), chromium (Cr), nickel (Ni), lead (Pb), cadmium (Cd), zinc (Zn), iron (Fe), and manganese (Mn), using atomic absorption spectrophotometry. The results were compared with the permissible limits set by the World Health Organization (WHO), Standards Organization of Nigeria (SON), and Federal Ministry of Environment (FME) regulations. The results revealed that iron and zinc were the dominant contaminants in the hand-dug wells in the study area. Both heavy metals exceeded the safe limits at more than 85% and 65%, respectively. Manganese also exceeded the safe limits at 75% of the sampling points. Geochemical source apportionment indicated that high levels of iron and manganese in the hand-dug wells in the study area were geogenic in origin. To evaluate the human health risk in the hand-dug wells in the study area, the Pollution Index (PI), Enrichment Factor (EF), Non-carcinogenic Hazard Quotient (HQ), Hazard Index (HI), and Carcinogenic Risk (CR) were calculated. The results revealed that the Hazard Index values for children were greater than 1.0 at 14 out of 20 sampling points. This indicated that non-carcinogenic risk existed in the hand-dug wells in the study area. The results also revealed that the Carcinogenic Risk values for lead ingestion by children exceeded the USEPA threshold value of 10⁻⁴ at four sampling points.